Analysis of Secure TCP/IP Profile in 61850 Based Substation Automation System for Smart Grids. (18th April 2016) - Khaled, Omar; Marín, Andrés; Almenares, Florina; Arias, Patricia; Díaz, Daniel
Abstract : Smart grid is the term used to describe modern power grids. It aims at achieving efficient, sustainable, economic, and secure delivery of electricity supplies. In order to achieve these goals, communication between different components within the grid and control centers is required. In a rapidly growing world, the demands for substation automation are increasing. Recently, two trends have been changing Substation Automation Systems: IEC 61850 and the need for cybersecurity. IEC 61850 specifies very strict performance requirements for message transfer time. The security for the smart grid must be designed to satisfy both performance and reliability requirements. In this paper, we address a study about secure communication in the substation real-time environment, complying with the IEC 61850 specifications. We mainly focus on analyzing the proposed Secure TCP/IP profile for MMS, testing different cipher suite combinations and examining whether by applying TLS we can still achieve the strict performance requirements of IEC 61850 or not. As a result of the study, we propose a list of cipher suite combinations that should be used. The importance of this study lies mainly on future scenarios, because IEC 61850 is thought to support smart metering communications.